US extended nuclear deterrence in Europe: Three scenarios. Crisis of trust, breach of trust and full disengagement - Liviu Horovitz (Stiftung Wissenschaft und Politik (SWP), 2025)
In recent months, there has been an intensifying debate over whether Europe can still rely on US extended nuclear deterrence or should begin to consider alternatives that are independent of Washington. A binary approach - trust or no trust - is of limited analytical value here; the subject matter demands greater differentiation. Accordingly, this paper presents three scenarios to allow for a better understanding of the key challenges and possible responses. The first scenario is a transatlantic crisis of trust that might be possible to address with moderate effort. The second is a breach of trust requiring increased conventional strength and the appropriate tools for escalation control in order to force the US to become involved if necessary. And the third scenario is one in which the Europeans conclude that the US has withdrawn its support completely - a development that would have far-reaching and unpredictable consequences.
Keywords: 320; USA; Europe; extended nuclear deterrence; nuclear shield; transatlantic relations; US President Donald Trump; France; United Kingdom; escalation dominance; escalation management; countervalue posture; mutually assured destruction; counterforce posture; damage limitation